A de novo TNNI3K variant aggravates the pathogenicity of DMD-associated early-onset cardiomyopathy: a case report - Qie, Di; Zhai, Yang; Yang, Fan; Li, Yifei; Xu, Rong (Frontiers in Genetics, 2025)
BackgroundDystrophin is a DMD coding protein that serves as a connector maintaining the structural formation and functional hemostasis of myofilaments, which regulate the contraction of cardiomyocytes. However, early-onset heart failure or cardiomyopathy is closely associated with adverse clinical outcomes in Duchenne muscular dystrophy (DMD)-affected patients. Pathogenicity screening and identification of the potential combined variants are thus critical for the management of such patients. Herein, we report a rare case of a patient with early-onset DMD attributed to a compound genetic variant in the DMD and TNNI3K genes.Case presentationThe proband, a 15-month-old male patient, presented with severe heart failure, enlarged ventricles, and diffuse fibrosis. Whole-exome sequencing was used to identify a compound missense variant as c.1540G>T (p.V514L) of the DMD gene and c.1633G>T of the TNNI3K gene, resulting in disease. The protein structures of the mutant dystrophin and TNNI3K were built using AlphaFold3. The amino acid residues around site 514 had changed in DMD p.V514L, and the altered surrounding structures resulted in protein dysfunction. Furthermore, the amino acid residues around site 545 had changed in TNNI3K p.G545C, causing significant alterations to the hydrogen bonding. As both of these mutations contribute to regulating the myofilaments, potential interactions are suspected. Then, the binding structure was established using AlphaFold3, and the structural changes were identified based on the compound variants.ConclusionWe present a rare case of a compound genetic variant that induces severe and very-early-onset heart failure in DMD patients. The compound variant attenuates the interactions between DMD and TNNI3K, leading to functional collapse of the myofilaments. This finding emphasizes the importance of comprehensive genetic analysis in DMD patients. Identification of additional variants can significantly aggravate the pathological process and disease prognosis, and such patients always require swift and careful clinical management to obtain desirable outcomes.